2008
DOI: 10.1007/s10265-008-0201-9
|View full text |Cite
|
Sign up to set email alerts
|

Activation of abscisic acid biosynthesis in the leaves of Arabidopsis thaliana in response to water deficit

Abstract: It is well known that endogenous abscisic acid (ABA) levels increase rapidly in response to drought stress and that this induces stomatal closure. In Arabidopsis thaliana, ABA levels increased rapidly in the leaves and roots when intact wild-type whole plants were exposed to drought stress. However, if the leaves and roots were separated and exposed to drought independently, the ABA level increased only in the leaves. These results suggest that, under our experimental conditions, ABA is synthesized mainly in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
112
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(119 citation statements)
references
References 42 publications
7
112
0
Order By: Relevance
“…Water deficit draws down water potential in all plant tissues and may directly impair turgor pressure in the guard cells surrounding the stomatal pores, thus reducing stomatal aperture (Buckley, 2005;Peak and Mott, 2011). In parallel, accumulation of ABA, whether synthesized in roots Borel et al, 2001) or leaves (Christmann et al, 2005(Christmann et al, , 2007Ikegami et al, 2009;McAdam et al, 2016), directly impacts on guard cells to close stomata (Kim et al, 2010;Joshi-Saha et al, 2011).…”
mentioning
confidence: 99%
“…Water deficit draws down water potential in all plant tissues and may directly impair turgor pressure in the guard cells surrounding the stomatal pores, thus reducing stomatal aperture (Buckley, 2005;Peak and Mott, 2011). In parallel, accumulation of ABA, whether synthesized in roots Borel et al, 2001) or leaves (Christmann et al, 2005(Christmann et al, , 2007Ikegami et al, 2009;McAdam et al, 2016), directly impacts on guard cells to close stomata (Kim et al, 2010;Joshi-Saha et al, 2011).…”
mentioning
confidence: 99%
“…Moreover, ectopic expression of a tomato NCED gene caused overproduction of ABA in tomato and tobacco (19). Over-expression of AtNCED3 in transgenic Arabidopsis and PvNCED1 in tobacco plants resulted in increased ABA accumulation and resistance to water stress (8,13). All of these results strongly suggest a key regulatory role of NCED in stress-induced ABA biosynthesis, at least in photosynthetic tissues.…”
Section: Introductionmentioning
confidence: 88%
“…These results indicated that the expression of AhNCED1 regulates ABA biosynthesis levels in peanut plants during water stress. The amino terminus of the AhNCED1 protein is basic and contains a high content of Ser and Thr residues characteristic of chloroplast transit peptides, similar to that of ZmVP14 (8,15), which is the key protein involved in abscisic acid synthesis in maize. In water-stressed Arabidopsis plants, AtNCED3 was exclusively detected by immunohistochemical analysis in the vascular parenchyma cells together with AtABA2 and AAO3 (5), which are also In order to better understand the distribution influence mechanism of ABA biosynthesis during different developmental stages, an investigation was carried out with an emphasis on characterizing the tissue-specific distribution of ABA in peanut during development, and the relationship and influence between tissue-specific distribution of ABA and tissue-specific expression of AhNCED1.…”
Section: Introductionmentioning
confidence: 99%
“…Abscisic acid (ABA) is an important plant hormone that regulates plant growth and development, participates in stress signal transduction, and improves plants' resistance to various stresses [1][2][3]. ABA can promote stomata closure and induce resistance protein synthesis through signal transduction of the defense cell membrane to enhance the resist ability of plant to stress, and also can regulate the expression of genes and proteins [3].…”
Section: Introductionmentioning
confidence: 99%